PERAN AUDIT COMMITTEE SEBAGAI PEMODERASI FAKTOR-FAKTOR YANG MEMENGARUHI FRAUDULENT FINANCIAL STATEMENT - Frecilia, Frecilia; Wijaya, Novia (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to provide empirical evidence about the influence of external pressure, changes in auditors, nature of industry, changes in directors, political connections of fraudulent financial statements through the audit committee as a moderating variabel. The second objective is to identify the influence of CEO education and effective monitoring on fraudulent financial statements. The population used in this study are companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The research sample was obtained through the purposive sampling method where there were 402 data that had been collected as samples. The data were analyzed using multiple regression methods to test the entire hypothesis. The results of this research indicate that external pressure has a negative impact on fraudulent financial statements. Therefore, the more significant the amount of debt obtained by a company, the more intensive the supervision conducted by creditors on the credit history of the company, and fraudulent activities can be detrimental to the company. The nature of the industry and effective monitoring have a positive impact on fraudulent financial statements. The audit committee strengthens the relationship between external pressure and fraudulent financial statements, while weakening the relationship between the nature of the industry and fraudulent financial statements. Moreover, changes in auditors, changes in directors, political connections, CEO education, changes in auditors moderated by the audit committee, changes in directors moderated by the audit committee, and political connections moderated by the audit committee have no significant influence on fraudulent financial statements.